Multiple primaries of head and neck: Adeno cystic carcinoma of the larynx with follicular carcinoma of the thyroid gland Case Report - Shem, Arsalan A. M.; Ali, Salah A.; Dabbagh, Lana Sh. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Adeno cystic carcinoma of the larynx is very rare and concomitantly with the follicular thyroid carcinoma is not reported in the literature. This case was presented to our centre because of the stridor and small anterior neck mass. Evaluation of the case showed a subglottic mass with an enhanced right thyroid mass on the CT scan. The treatment was thyroidectomy followed by total laryngectomy and bilateral neck dissection. The histopathological study of the subglottic mass showed adeno cystic carcinoma and of the thyroid mass was follicular carcinoma. The adeno cystic carcinoma of the larynx is usually asymptomatic and it has the opportunity to invade deeply before the diagnosis. Proper evaluation of the head and neck is mandatory in any laryngeal lesion.